Kepemimpinan Hibrida dalam Resolusi Konflik Lokal: Model Mediasi Berbasis Nilai Ghengghu’ dan Legitimasi Sosial Blater - Naqiah Naqiah; Agung Dwi Bahtiar El Rizaq; Mohammad Ali Al Humaidy; Heni Listiana (Universitas Tribhuwana Tungga Dewi, 2026)
Social conflicts in Madurese society are deeply intertwined with the value of ghengghu’ (honor) as a moral foundation for preserving human dignity and community relations. Consequently, dispute resolution mechanisms do not rely solely on formal judicial systems, but also actively involve informal figures such as blater, who hold strong social legitimacy. This study aims to analyze the role of blater as conflict mediators and to formulate a social reconciliation model grounded in local wisdom in Candi Village, Dungkek District, Sumenep Regency. The research site was selected purposively due to the persistent, significant social influence of blater figures in local community governance. Utilizing a qualitative approach with a case study design, data were gathered through in-depth interviews with key informants (blater, village officials, community leaders, and disputing parties), participant observation, and documentary analysis of village mediation records. The findings indicate that the legitimacy of blater derives from moral integrity, social proximity, and the capacity to safeguard communal dignity. Blater function as dialogue facilitators and intermediaries connecting informal leadership with formal village bureaucratic institutions. This study formulates a conceptual model of